2015
DOI: 10.1016/j.virol.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-exposure safety and efficacy of attenuated rabies virus vaccines are enhanced by their expression of IFNγ

Abstract: Consistent with evidence of a strong correlation between interferon gamma (IFNγ) production and rabies virus (RABV) clearance from the CNS, we recently demonstrated that engineering a pathogenic RABV to express IFNγ highly attenuates the virus. Reasoning that IFNγ expression by RABV vaccines would enhance their safety and efficacy, we reverse-engineered two proven vaccine vectors, GAS and GASGAS, to express murine IFNγ. Mortality and morbidity were monitored during suckling mice infection, immunize/challenge e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…While there is evidence of a mechanism that transiently allows peripheral antibody to reach the CNS during infection of normal mice with attenuated RABV (38), we do not know whether or not this is operative in T-bet −/− mice and the kinetics of antibody accumulation in sera do not entirely parallel virus clearance from the CNS of these animals. On the other hand, the production of IFN-γ in CNS tissues has been found to strongly inhibit attenuated RABV replication independently of antibody, likely through the enhanced expression of innate antiviral agents (22). IFN-α expression was most closely related to IFN-γ-induced antiviral effects while the induction of IFN-β appeared to be more a consequence of viral replication (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is evidence of a mechanism that transiently allows peripheral antibody to reach the CNS during infection of normal mice with attenuated RABV (38), we do not know whether or not this is operative in T-bet −/− mice and the kinetics of antibody accumulation in sera do not entirely parallel virus clearance from the CNS of these animals. On the other hand, the production of IFN-γ in CNS tissues has been found to strongly inhibit attenuated RABV replication independently of antibody, likely through the enhanced expression of innate antiviral agents (22). IFN-α expression was most closely related to IFN-γ-induced antiviral effects while the induction of IFN-β appeared to be more a consequence of viral replication (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, cells producing IFN-γ control virus replication, evidently through the enhanced induction of type 1 interferons and other innate antiviral mechanisms (22, 23). This explains why mice with T cells but no functional B cells can control attenuated RABV infection and survive for extended periods of time while mice lacking both T and B cells succumb (24).…”
Section: Introductionmentioning
confidence: 99%
“…Rabies is a public health threat that causes more than 59,000 human deaths around the world each year, and most of these deaths occur in the developing countries of Asia and Africa (1,2). Globally, over 3 billion humans are threatened with exposure to rabies because they live in areas where rabies is endemic in domestic or wild animals (3).…”
mentioning
confidence: 99%
“…Further investigation using knockout mice unable to signal through the type I IFN receptor indicated that the recombinant RABV expressing IFN-g strongly attenuates the pathogenicity via induction of type I IFN [68] . A subsequent study found that the incorporation of the murine IFN-g gene in a highly attenuated GAS backbone can enhance safety and immunogenicity [69] .…”
Section: Evidence That Rabies Virus Expression Of Chemokine/cytokine mentioning
confidence: 99%